Genes Involved in Maintaining Mitochondrial Membrane Potential Upon Electron Transport Chain Disruption - Vasan, Karthik; Clutter, Matt; Fernandez Dunne, Sara; George, Mariam D.; Luan, Chi-Hao; Chandel, Navdeep S.; Martínez-Reyes, Inmaculada (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are biosynthetic, bioenergetic, and signaling organelles with a critical role in cellular physiology. Dysfunctional mitochondria are associated with aging and underlie the cause of a wide range of diseases, from neurodegeneration to cancer. Through signaling, mitochondria regulate diverse biological outcomes. The maintenance of the mitochondrial membrane potential, for instance, is essential for proliferation, the release of mitochondrial reactive oxygen species, and oxygen sensing. The loss of mitochondrial membrane potential triggers pathways to clear damaged mitochondria and often results in cell death. In this study, we conducted a genome-wide positive selection CRISPR screen using a combination of mitochondrial inhibitors to uncover genes involved in sustaining a mitochondrial membrane potential, and therefore avoid cell death when the electron transport chain is impaired. Our screen identified genes involved in protein translation and ATP synthesis as essential for the induction of cell death when cells lose their mitochondrial membrane potential. This report intends to provide potential targets for the treatment of diseases associated with mitochondrial dysfunction.